Meningkatkan Kemampuan Melipat Pakaian bagi Anak Tunagrahita Sedang di Wisma Setaman Dalam Bhakti Luhur Malang - Siribere, Margaretha Jayusni; Selatang, Fabianus (Jurnal Pelayanan Pastoral, 2023)
This study aims to describe the implementation of clothes folding skills for children with moderate intellectual impairment. Children with special needs (ABK) are children who experience limitations both physically, mentally-intellectually, socially, and emotionally, which significantly affect the process of growth or development compared to normal children their age. Intellectual impairment is a condition of children whose intelligence is below the average of normal children and is characterized by limitations in terms of intelligence and incompetence in social communication. This paper aims to identify and apply the ability to fold clothes to moderately disabled children living in Wisma Setaman Dalam. The method carried out by the author is observation, especially to make provisions for exercise activities for children with special needs. To support the above data, the author also conducted an interview with one of the persons in charge of the homestead who has expertise in the field of moderately mentally impaired children. After going through these processes, the author found a provision for training activities that were suitable for the circumstances and children with special needs. The next step, the predetermined training activities are carried out according to the schedule made so far.